Busana Muslim di Kalangan Generasi Muda: Antara Gaya Hidup Identitas dan Pendidikan Karakter Islami - Muthia Azzahra; Muhammad Ziqra Rahsa; Mulya Darma Illahi; Ridwal Trisoni; Muhammad Yahya (Al-Abshor : Jurnal Pendidikan Agama Islam, 2026)
This study explores the phenomenon of Muslim and Muslimah fashion among today’s youth, focusing on its role in shaping religious identity and character education in the modern era. In recent years, the rise of social media platforms such as TikTok and Instagram has contributed to the widespread popularity of “modest fashion” and “hijrah lifestyle” trends among young Muslims. However, many previous studies have primarily emphasized the aesthetic and commercial aspects of Islamic fashion, leaving a gap in understanding how clothing practices relate to moral and educational development. This research aims to address that gap by examining the connection between Islamic dress, youth identity, and the values of Islamic character education. Using a qualitative descriptive approach, data were collected through literature review and analysis of social media content that reflects youth fashion behavior. The findings indicate that Muslim attire is not merely a matter of style but serves as a medium for self-expression, religious commitment, and social influence. Nevertheless, the study also reveals that some young people adopt Islamic dress for trend-related reasons without a deep understanding of its spiritual meaning. The implications suggest that educational institutions should integrate Islamic values into character education programs to balance external appearance with internal piety. In conclusion, this study highlights the importance of guiding the younger generation to view Islamic clothing not only as a fashion statement but as an embodiment of moral and religious identity.     Abstract This study explores the phenomenon of Muslim and Muslimah fashion among today's youth, focusing on its role in shaping religious identity and character education in the modern era. In recent years, the rise of social media platforms such as TikTok and Instagram has contributed to the widespread popularity of “modest fashion” and “hijrah lifestyle” trends among young Muslims. However, many previous studies have primarily explained the aesthetic and commercial aspects of Islamic fashion, leaving a gap in understanding how clothing practices relate to moral and educational development. This research aims to address that gap by examining the connection between Islamic dress, youth identity, and the values ​​of Islamic character education. Using a qualitative descriptive approach, data were collected through literature review and analysis of social media content that reflects youth fashion behavior. The findings indicate that Muslim attire is not merely a matter of style but serves as a medium for self-expression, religious commitment, and social influence. Nevertheless, the study also revealed that some young people adopt Islamic dress for trend-related reasons without a deep understanding of its spiritual meaning. The implications suggest that educational institutions should integrate Islamic values ​​into character education programs to balance external appearance with internal piety. In conclusion, this study highlights the importance of guiding the younger generation to view Islamic clothing not only as a fashion statement but as an embodiment of moral and religious identity.